Provisions for tracking transferred fraudulently - قادر حاجي, ئاوات عمر (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The movable has an important role in people’s financial transactions، and it is a given، so providing the necessary support in the event that it leaves the hands of its owner without his consent، i.e. without a right (such as his leaving with theft، usurpation، breach of trust، loss and fraud) is a very important matter by which the stability of transactions and the realization of the right is achieved. At the same time، and due to the nature of the movable، the movable may reach someone’s hand for a valid reason without knowing that he is infringing the rights of what you have. Article 1164 of the Civil Code answers that the owner may recover it within three years from the time of the accident، but it did not mention the case of the move out of the movable by fraud، so what is the ruling in this case? Does it have the same ruling mentioned above for the union of the cause or a cause for both based on analogy? Or that the ruling is different and that the holder has to adhere to the rule of possession of the movable in good faith and because of the correct title deed stipulated in Article 1163 of the Civil Code? Why did the Iraqi legislator not mention fraud within the cases mentioned in Article 1164 despite the unity of the cause or the union of the cause? The answer to this question is the subject of this research، and in conclusion، the research came up with a proposal to amend Article 1164 in order to solve this problem.